A Study of Nutrition in Entry‐Level Dental Hygiene Education Programs. Issue 1 (1st January 2016) - Johnson, Deborah L.; Gurenlian, JoAnn R.; Freudenthal, Jacqueline J.
Abstract : The aims of this study were to document the extent of nutritional content in U.S. dental hygiene program curricula; identify program directors' opinions, perceptions, and barriers to expanding nutritional content; and evaluate if a proposed nutrition curriculum model would be beneficial. This mixed methods study involved quantitative and qualitative aspects. An invitation letter was sent to all 335 directors of entry‐level U.S. dental hygiene programs. In response, 55 directors submitted nutrition course syllabi from their programs (16.4% of the total) for the quantitative analysis. In addition, 14 nutrition instructors and ten program directors were interviewed regarding their perceptions and opinions of nutrition education for dental hygiene students. All aspects of the content analysis results revealed that nutrition content in entry‐level dental hygiene programs is diverse. Some programs did not include nutrition content, while others provided oral and systemic nutrition intervention subject matter. Some programs offered multiple clinical nutrition applications and patient contact opportunities while most required none. The interview results disclosed a variety of opinions and perceptions of dental hygienists' role in nutrition. Several interviewees viewed dental hygienists' role in nutrition to be an integral part of patient care, while others indicated no role or providing caries prevention counseling only. Although dental hygienists are expected to provide nutrition assessments and interventions, no standards or standardized competencies exist for nutrition in dental hygiene education. A standardized nutrition model could be beneficial for entry‐level programs to ensure dental hygienists possess basic knowledge to perform nutrition assessments and intervention to address Healthy People 2020's intervention initiatives.